The cluster beam route to model catalysts and beyond. (6th May 2016) - Ellis, Peter R.; Brown, Christopher M.; Bishop, Peter T.; Yin, Jinlong; Cooke, Kevin; Terry, William D.; Liu, Jian; Yin, Feng; Palmer, Richard E.
Abstract : The generation of beams of atomic clusters in the gas phase and their subsequent deposition (in vacuum) onto suitable catalyst supports, possibly after an intermediate mass filtering step, represents a new and attractive approach for the preparation of model catalyst particles. Compared with the colloidal route to the production of pre-formed catalytic nanoparticles, the nanocluster beam approach offers several advantages: the clusters produced in the beam have no ligands, their size can be selected to arbitrarily high precision by the mass filter, and metal particles containing challenging combinations of metals can be readily produced. However, until now the cluster approach has been held back by the extremely low rates of metal particle production, of the order of 1 microgram per hour. This is more than sufficient for surface science studies but several orders of magnitude below what is desirable even for research-level reaction studies under realistic conditions. In this paper we describe solutions to this scaling problem, specifically, the development of two new generations of cluster beam sources, which suggest that cluster beam yields of grams per hour may ultimately be feasible. Moreover, we illustrate the effectiveness of model catalysts prepared by cluster beam deposition onto agitated powders in the selective hydrogenation of 1-pentyne (a gas phase reaction) and 3-hexyn-1-ol (a liquid phase reaction). Our results for elemental Pd and binary PdSn and PdTi cluster catalysts demonstrate favourable combinations of yield and selectivity compared with reference materials synthesised by conventional methods.